Science, technology and innovation in the context of development: An overview of concepts and corresponding policies recommended by international organisations - Anna Schwachula; Maximiliano Vila Seoane; Anna-Katharina Hornidge (University of Bonn, Center for Development Research (ZEF), 2014)
Beyond the impact that Science, Technology and Innovation (ST&I) have for creating knowledgebased economies, they may also contribute to social and ecological dimensions of development. This would require beneficial ST&I policies to be in place. While authors have studied single ST&I impacts, scientific overviews of the entire range of possible impacts of ST&I and its policies are currently still lacking. In our paper on "Science, technology and innovation in the context of development - an overview of concepts and corresponding policies" we therefore present different scientific models and conceptions of how ST&I contribute to different aspects of development. After a first introduction to ST&I in the context of development and the role of policies, we group scientific models and conceptions into three ideal-type categories: ST&I for economic development, ST&I for sustainable development and ST&I for inclusive development. In addition to outlining underlying scientific concepts, we focus on the recommendations for ST&I policies of OECD, World Bank and UNESCO that correspond to each category. In the concluding section, we discuss the role of the ST&I policy models issued by international organisations and discuss how far they are transferrable to developing countries.
Keywords: 330; Science; Technology; Innovation; Science Policy; Sustainability; Social development; economic development